Conceptualized and development of preliminary strategic procurement planning analysis outline for Local Government Engineering Department (LGED) - Raihan, Md. Abu (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2023.